Image of Synthetic Biology and Nanotechnology: A Survey among University Students - Ineichen, Christian; Biller-Andorno, Nikola; Deplazes-Zemp, Anna (Frontiers in Genetics, 2017)
This study explores the image of synthetic-biology and nanotechnology in comparison to agricultural biotechnology and communication-technology by examining spontaneous associations with, and deliberate evaluations of, these technologies by university students. Data were collected through a self-completion online questionnaire by students from two universities in Switzerland. The survey aimed to capture implicit associations, explicit harm-benefit-evaluations and views on regulation. The data suggest overall positive associations with emerging technologies. While positive associations were most pronounced for nanotechnology, agricultural biotechnology was attributed with the least favourable associations. In contrast to its positive result in the association task, respondents attributed a high harm potential for nanotechnology. Associations attributed to synthetic-biology were demonstrated to be more positive than for agricultural biotechnology, however, not as favourable as for nanotechnology. Contrary to the evaluations of nanotechnology, the benefit-examples of synthetic-biology were evaluated particularly positively. Accordingly, the investigated technologies enjoy different esteem, with synthetic biology and nanotechnology both showing a more “exciting” image. Even though the image of nanotechnology was demonstrated to be more pronounced it was also more heterogeneous across tasks while agricultural biotechnology remains contested. For all technologies, the predominant spontaneous concerns pertain to risks rather than an immoral nature inherent to these technologies. Our data suggest that harm-benefit-analyses reveal only one aspect of the attitude towards emerging technologies. Survey questions addressing spontaneous associations with these technologies are a valuable addition to our picture of the image of emerging technologies.